Orchid Mycorrhizal Fungi Combination to Overcome Water Stress in Dendrobium Spectabile Orchids (Biosaintifika: Journal of Biology & Biology Education, 2026)
One strategy to mitigate drought stress is using orchid mycorrhizal fungi (OMF) of the Rhizoctonia type. This study aims to determine the use of a combination of Rhizoctonia mycorrhiza isolated from the roots of two Dendrobium orchid species and watering intervals on Dendrobium spectabile seedlings. The research method used was a randomized block design (RBD) with 2 factors and 5 replications: the first factor was inoculation of OMF isolated from the roots of Dendrobium fimbriatum (D1), Dendrobium phalaenopsis (D2), and a combination of OMF D1 + D2 (D3). The second factor included watering intervals every 2-days (W1), 4 days (W2), and every 6-days (W3). The results showed that OMF inoculation factors on D. spectabile gave significantly different results on plant height, leaf length, root length, plant fresh weight, and plant dry weight, with the best results using the OMF combination (D3). The watering interval factor gave significantly different results on plant height and number of roots, with the best results on watering every 4-days (W2). The highest chloroplast content was found in D3W3 (0.89), while proline accumulation reached its peak at D2W3 (0.135). Microscopic observations confirmed the formation of pelotons in the root cortex. Overall, the combined OMF inoculum applied with a 4-day watering interval (D3W2) is a promising approach to improve drought tolerance in D. spectabile seedlings. This research supports SDG 15 (Life on Land Ecosystems), as a solution to overcome water stress, the main cause of desertification and land degradation that affects the growth of orchid species in nature.